Periodontal clinical status, microbial profile, and expression of interleukin-1β in men under androgenic anabolic steroids abuse - von Stein Cubas Warnavin, Stephanie; Valenga, Henrique Meister; Costa, Thainá Biudes Conforto; Chaves, Joao Daniel Paganella; Spolidorio, Luis Carlos [UNESP]; Spolidorio, Denise Madalena Palomari [UNESP]; Feres, Magda; Soares, Geisla Mary Silva; Steffens, Joao Paulo (Springer Nature, 2021)
Objectives: Androgenic anabolic steroids (AAS) abuse is a serious health problem associated to several systemic complications. Here, we evaluated the periodontal clinical status, microbial profile, and expression of total protein (TP) and interleukin (IL)-1β in men using AAS. Materials and methods: Men using AAS were recruited (case group) and matched for age with men who had never used AAS (control group) but also performed physical activities. Plaque index (PI), marginal bleeding (MB), probing depth (PD), clinical attachment level (CAL), and bleeding on probing (BoP) were evaluated. Crevicular fluid and subgingival biofilm were collected from healthy and diseased sites (PD ≥ 4 mm with CAL ≥ 1 mm and BoP) and evaluated for TP, IL-1β, and proportions of 40 bacterial species. Results: Thirty patients were included (n = 15/group). AAS consumers had significantly higher mean PD and higher percentage of diseased sites; sites with PD ≥ 4 mm or with CAL ≥ 1 mm than non-consumers. Also, AAS users showed a more dysbiotic biofilm containing lower proportions of host-compatible species and higher proportions of pathogens. IL-1β expression was statistically higher in diseased than in healthy sites only in the control group. A statistically positive correlation was detected between periodontal pathogens and IL-1β expression. The number of AAS cycles was positively associated with higher percentages of periodontal pathogens, but not with IL-1β or total protein concentrations. Conclusions: AAS intake can worsen clinical and immunological periodontal conditions and the biofilm composition in healthy sites. Clinical relevance: Dental care professionals should perform full mouth periodontal screening and schedule regular follow-up appointments for patients under AAS use.
Keywords: Periodontitis; Periodontium; Steroids; Testosterone